Global occupational health - Guidotti, Tee L, Ed (Oxford University Press, 2011)
'Global Occupational Health' is a comprehensive introductory textbook designed for the preparation of professionals in occupational health. The textbook is intended for use in basic to mid-level courses, providing the reader or student with a solid foundation from which to pursue more specialized studies.